Terrestrial gamma radiation dose rates (TGRD) from surface soil in Negeri Sembilan, Malaysia - Norbani, Nor Eliana (Elsevier, 2014)
Baseline data on background radiation levels allows for future assessment of possible changes in natural radionuclide concentrations, either as a result of geological processes or radioactive contamination. We have measured terrestrial gamma radiation dose-rates (TGRD) from surface soils throughout accessible areas in the Peninsular Malaysia state of Negeri Sembilan (NS). Dose rate measurements were carried out using a Nal (TI) scintillation survey meter, encompassing 1708 locations, covering about 73% of the 6645 km2 of the land area in NS. This has allowed development of a TGRD contour map, plotted using WinSurf software. The range of measured TGRD was from 71 +/- 3 nGy/h up to 1000 +/- 11 nGy/h. The greatest measured TGRD was obtained in an area covered by soil types originating from igneous rock of granitic formations, while the least value of TGRD was observed in an area covered by limestone composed of calcite mineral, mostly found near river and coastal areas. Mean values of TGRD across the seven districts of NS ranged from 244 +/- 7 nGy/h to 458 +/- 13 nGy/h, the global mean being 330 +/- 8 nGy/h compared to a mean value of 92 nGy/h and 59 nGy/h for Malaysia and the world, respectively. The average annual dose from such terrestrial gamma radiation dose-rates to an individual residing in NS, assuming a tropical rural setting, is estimated to be 0.96 mSv per year.